Short and long-term effects of leucine and branched-chain amino acid supplementation of a protein and energy reduced diet on muscle protein metabolism in neonatal pigs - Manjarín, Rodrigo (Amino Acids, 2018)
The objective of this study was to determine if enteral leucine or branched-chain amino acid (BCAA) supplementation increases muscle protein synthesis in neonates who consume less than their protein and energy requirements, and whether this increase is mediated via the upregulation of the mammalian target of rapamycin (mTOR) pathway or the decrease in muscle protein degradation signaling. Neonatal pigs were fed milk replacement diets containing reduced energy and protein (R), R supplemented with BCAA (RBCAA), R supplemented with leucine (RL), or complete protein and energy (CON) at 4-h intervals for 9 (n = 24) or 21 d (n = 22). On d 9 and 21, postprandial plasma amino acids and insulin were measured at intervals for 4 hr; muscle protein synthesis rate and activation of mTOR-related proteins were determined at 120 min post-feeding in muscle. For all parameters measured, the effects of diet were not different between d 9 or d 21. Compared to CON and R, plasma leucine and BCAA were higher (P ≤ 0.01) in RL- and RBCAA-fed pigs, respectively. Body weight gain, protein synthesis, and activation of S6 kinase (S6K1), 4E-binding protein (4EBP1), and eukaryotic initiation factor 4 complex (eIF4E·eIF4G) were decreased in RBCAA, RL, and R relative to CON (P < 0.01). RBCAA and RL upregulated (P ≤ 0.01) S6K1, 4EBP1 and eIF4E·eIF4G compared to R. In conclusion, when protein and energy are restricted, both leucine and BCAA supplementation increase mTOR activation but do not enhance skeletal muscle protein synthesis and muscle growth in neonatal pigs.